The correlation between the demographic profile and continuing professional education of academic librarians in Metro Manila - Tabiendo, Grace B. (School of Library and Information Studies, University of the Philippines Diliman, 2003)
Continuing professional education is the process of engaging in educational pursuits with the goal of becoming up-to-date in the knowledge and skills of one's profession. The study aimed to determine the relationship between the demographic profile and the choice of continuing professional education programs/activities of academic librarians in Metro Manila. Eighty (80) licensed librarians of the 20 academic libraries were the subjects of the study.